Linear and Riccati matrix equations - Lloyd K. Williams (International Journal of Mathematics and Mathematical Sciences)
In this paper we find exact solutions for linear ordinary differential equations of any order when they are given in matrix form, as well as for classes of Riccati matrix equations with two or three arbitrary matrix coefficients. Other nonlinear systems of triangular form are also solved completely.